The Effect of Core Stability Training Variations on Crescent Kick Speed in Pencak Silat Athletes at SMPN 29 Medan - Manihuruk, Hotmaon Tio Raja Br; Siahaan, David (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2025)
This study aimed to investigate the impact of core stability training variations on the speed of the crescent kick among Pencak Silat athletes from the Lapan Penjuru club at SMPN 29 Medan in 2024. Lapan Penjuru is a dedicated Pencak Silat training program integrated into the school. The research employed an experimental method using a one-group pretest-posttest design. The population consisted of 20 student-athletes, from which 8 participants were selected through purposive sampling. The training intervention was conducted over six weeks, with sessions held three times a week. Data analysis using a paired-sample t-test revealed a calculated t-value (tₒ) of 10.93, which exceeds the critical t-table value of 1.89 at a significance level of α = 0.05 with 7 degrees of freedom. These results led to the rejection of the null hypothesis (H₀) and the acceptance of the alternative hypothesis (Hₐ). Therefore, it can be concluded that variations in core stability training have a significant positive effect on improving crescent kick speed among Pencak Silat athletes at SMPN 29 Medan.